Beyond Bandung: the 1955 Asian-African Conference and its legacies for international order. Issue 4 (3rd July 2016) - Phillips, Andrew
ABSTRACT: The special issue this article opens examines the systemic impact, limits, achievements and legacies of the 1955 Asian-African 'Bandung' Conference. The Bandung conference is typically celebrated as a high point of Indonesian foreign policy activism and a key milestone in the emergence of the 'Third World'. By contrast, mainstream international relations has paid comparatively less attention to its broader impact in the evolution of the modern international order. The special issue contributors here seek to correct this lacuna by interrogating Bandung's significance in challenging, affirming and amending key aspects of the post-war global order. They also consider its relevance in setting important precedents that simultaneously foreclosed and enabled different manifestations of South–South cooperation thereafter. Beyond its historical significance, they finally explore Bandung's enduring legacies for both domestic Indonesian order-building projects and Indo-Australian efforts to bridge the 'Bandung divide' in their responses to contemporary threats to international order. This article opens this inquiry by historically situating Bandung within its broader global context, unpacking its four 'faces' (order-challenging, order-affirming, order-building and order-transforming) and finally delineating the key axes of debate around which this special issue is organised.